Implementation of Game Methods to Improve Pancasila Knowledge and Attitudes of Elementary School Students in Sampang - Mustain Mustain; Munir Munir (FASHLUNA, 2026)
This study aims to examine the effectiveness of game-based learning in improving students' knowledge and attitudes toward Pancasila values in Pancasila Education for third-grade students at UPTD SDN Ketapang Barat 4. The study employed a classroom action research approach using the model of Stephen Kemmis and Robin McTaggart, which includes planning, action, observation, and reflection stages conducted in two cycles. The research participants consisted of 25 students. Data were collected through summative tests to measure cognitive achievement, attitude questionnaires to assess affective aspects, and observation sheets to record student participation and interaction during learning activities. The results indicate that the success criteria were not achieved in the first cycle due to limited student participation and incomplete implementation of the learning process. After improvements in the second cycle, the class average score increased from 81.12 to 83.84, and learning mastery improved from 60% to 100%. In addition, students' positive attitudes toward Pancasila values reached 85.2%–93.0%. These findings indicate that game-based learning effectively enhances student engagement, knowledge acquisition, and attitudes in Pancasila Education .